Factors Associated with Use of Evidence-Based Practice Strategies in Usual Care Youth Psychotherapy - Brookman-Frazee, Lauren (Springer US, 2009)
The purpose of this study was to gain an understanding of how therapists providing usual care (UC) psychotherapy are using elements of treatment common to evidence-based practices (EBPs) for children with disruptive behavior disorders (DBPs) and to identify client and therapist characteristics that may be associated with EBP strategies directed toward children and those directed to their caregivers. Results indicate that certain child, family, and therapist characteristics are associated with use of EBP strategies; however, much of the variability in practice was not explained by the variables examined. These findings highlight the complexity of UC psychotherapy and provide directions for future research on implementation of EBPs in UC.